Aβ seeds and prions: How close the fit?. Issue 4 (4th July 2017) - Rasmussen, Jay; Jucker, Mathias; Walker, Lary C.
ABSTRACT: The prion paradigm is increasingly invoked to explain the molecular pathogenesis of neurodegenerative diseases involving the misfolding and aggregation of proteins other than the prion protein (PrP). Extensive evidence from in vitro and in vivo studies indicates that misfolded and aggregated Aβ peptide, which is the probable molecular trigger for Alzheimer's disease, manifests all of the key characteristics of canonical mammalian prions. These features include a β-sheet rich architecture, tendency to polymerize into amyloid, templated corruption of like protein molecules, ability to form structurally and functionally variant strains, systematic spread by neuronal transport, and resistance to inactivation by heat and formaldehyde. In addition to Aβ, a growing body of research supports the view that the prion-like molecular transformation of specific proteins drives the onset and course of a remarkable variety of clinicopathologically diverse diseases. As such, the expanded prion paradigm could conceptually unify fundamental and translational investigations of these disorders.